Quy trình xây dựng trợ giảng AI hỗ trợ giáo viên trong dạy học sinh học ở trường phổ thông - Lê, Minh Thư; Trương, Thùy Phương; Phan, Thị Thanh Hội; Trần, Thị Giang Châu (Tạp chí Giáo dục, 2025)
The proactive adaptation of teachers to technological progress is considered a decisive factor for the development of education in the digital age. This study presents the design of BioAI-an augmented AI Chatbot used as a teaching assistant for Biology teachers, while providing accurate feedback to personalize student learning. 44 teachers and 414 students were surveyed, in which 82.6% of the teachers expressed a willingness to integrate BioAI into their teaching practices and 91.55% of students rated the practical value of this tool in supporting learning highly. Research has proposed a four-step process for developing an AI Chatbot: (1) Identifying the purpose and usage requirements of the Chatbot; (2) Determining the database; designing the AI Chatbot; (3) Consulting with experts; (4) Publishing and managing the Chatbot. Based on this proposed framework, BioAI has been designed and implemented in practical applications. The findings confirm the feasibility and effectiveness of applying enhanced AI in biology education and propose the broader deployment of BioAI in education to foster students’ self-directed learning competencies and promote pedagogical innovation.